2015
DOI: 10.3748/wjg.v21.i17.5407
|View full text |Cite
|
Sign up to set email alerts
|

IsHelicobacter pyloriinfection associated with glycemic control in diabetics?

Abstract: H. pylori infection is associated with poorer glycemic control in T1DM patients, but eradication may not improve glycemic control in DM in a short-term follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 41 publications
3
47
2
2
Order By: Relevance
“…However, a recent meta‐analysis reported that no solid evidence is available for the worsening of T2DM control by H. pylori infection, and no consensus has been reached. With regard to H. pylori eradication, it has been reported that eradication does not improve the T2DM control status, and H. pylori eradication is more likely to fail in DM (including type 1 DM) patients than in non‐DM patients . Moreover, eradication has been reported to improve insulin resistance in patients with a type B insulin receptor abnormality, a subtype of DM .…”
Section: Indicationsmentioning
confidence: 99%
“…However, a recent meta‐analysis reported that no solid evidence is available for the worsening of T2DM control by H. pylori infection, and no consensus has been reached. With regard to H. pylori eradication, it has been reported that eradication does not improve the T2DM control status, and H. pylori eradication is more likely to fail in DM (including type 1 DM) patients than in non‐DM patients . Moreover, eradication has been reported to improve insulin resistance in patients with a type B insulin receptor abnormality, a subtype of DM .…”
Section: Indicationsmentioning
confidence: 99%
“…The incidence of positivity increased with age. The number of positive cases were more in males (n-18, 36.7%) then females (7,22.6%) p-0.18 (Table 1). When compared with HbA1C levels mean HbA1C was higher in the H. Pylori positive group 7.92±2.1 vs. 7.51±1.5, p=0.34 (Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…Similar association has been found in many previous studies. 6,7 Long duration of disease, poor hygiene and poor glycaemic control has been associated with diabetes in positive cases. 8,9 There has been association of awareness of disease and the association of H. Pylori positivity in cases of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Camel milk is also rich in amino acids including valine, methionine, lysine, arginine and phenylalanine. It also contains high amounts of albumin and globulin (3). The aim of this study is to investigate the in vitro antagonistic effects of probiotics isolated from camel milk on the growth of clinical strains of H. pylori resistant to selective agents.…”
mentioning
confidence: 99%